Giving Deference to Inaction: How Geddes v. United Staffing Alliance Employee Medical Plan Compromised an Employee's Right to Meaningful Review Under ERISA - Erin Nave (Washington University Journal of Law & Policy, 2009)
This Note proposes that the arbitrary and capricious standard of review should be eliminated in favor of a de novo standard of review in all benefits denial cases.
Keywords: Judicial review; Employee fringe benefits; Employee benefits; Judicial discretion; Employee Retirement Income Security Act of 1974; Geddes v. United Staffing Alliance Employee Medical Plan